PERILAKU PENGUNJUNG PADA OBJEK WISATA AIR PANAS SUAMAN DI DESA PAWAN KECAMATAN RAMBAH KABUPATEN ROKAN HULU PROVINSI RIAU - Afe Risnan; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purpose to determine behaviour Of The visitors as a tourist object Air Panas Suaman in Pawan Village Rambah districts Rokan Hulu district Riau Province.This research uses a descriptive quantitative method to study the issue discussed. The sample in this research is 100 respondents which were taken by using accidental sampling. While data collection techniques in this research using observation, questionnaire by using a likert scale as a measure to determine the length of the short interval.Based on the research that has been done, behaviour Of The visitors as a tourist object Air Panas Suaman in Pawan Village Rambah districts Rokan Hulu district Riau Province. are included in the category of less agree, because Air Panas Suaman many deficiency.Keywords : Behaviour Visitors ,Tourism, Rokan Hulu district, Air Panas Suaman